LIBRARY 2.0 DAN DAMPAKNYA DALAM PENGEMBANGAN APLIKASI DAN LAYANAN PERPUSTAKAAN - Wicaksono, Hendro (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2010)
This article discusses about Library 2.0 and its implications for conventional library services. It explores the implementation of this program in libraries with popular information technology (IT) services, including Mashup dan Web Service, Online Social Networking (OSN), and user based taxonomy.